Single-cell identification by microfluidic-based in situ extracting and online mass spectrometric analysis of phospholipids expression. Issue 1 (18th November 2019) - Huang, Qiushi; Mao, Sifeng; Khan, Mashooq; Li, Weiwei; Zhang, Qiang; Lin, Jin-Ming
Abstract : A microfluidic-based in situ single-cell recognition system (ISCRS) to analyze phosphatidylcholines for the cells classification. Abstract : This work describes a microfluidic system for in situ extraction of a single-cell and its phosphatidylcholine analysis through mass spectrometry. This approach uncovered cellular heterogeneity among seemingly identical cells and provided a new platform for identification and classification of cells.